PHASIS OF NIKOLAI PIROGOV. THE STAGES OF SPIRITUAL EVOLUTION - G. G. Khubulava (Дискурс, 2016)
This article analyzes the development of religious views of the surgeon and public figure Nikolai Pirogov. Boldness in the battle with patient's ailments, humility, manifested in detachment towards glory and honor, and in a constant desire to learn new. All this is often more difficult to a physician who does not decide a question of his attitude to people, in its ultimate form reduced to the question of relationship with God.